1985
DOI: 10.1111/j.1399-3054.1985.tb03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorate‐resistant rose cells: influx, efflux and reduction of [36Cl]‐chlorate

Abstract: Clones of Rosa damascena Mill. cv. Gloire de Guillan, selected for growth in solid medium containing 56 mM NaClO3, were studied to determine the reason for their resistance to this toxic salt. The cells grew on medium containing nitrate as the only nitrogen source, and they synthesized nitrate reductase (EC 1.6.6.2) in the presence of nitrate. The cells were resistant in the presence of nitrate. However, their resistance was greatly increased by the presence of glutamate in the medium. The cells took up [36Cl]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Characterization of chlorate-resistant mutants has primarily focused on those which are nitrate reductase-deficient. Chlorate-resistant mutants which possess nitrate reductase activity have been identified, and a number of alternative mechanisms of resistance have been discussed (Oostindier-Braaksma and Feenstra 1973, Cove 1979, Murphy et al 1985), There appears to be, however, only two published reports characterizing chlorate uptake mutants. Doddema and Telkamp (1979) reported that a chlorate-resistant, CIO; uptake mutant of Arabidopsis thaliana was impaired in NO; uptake relative to the wild type at higher nitrate concentration ranges.…”
Section: Resultsmentioning
confidence: 99%
“…Characterization of chlorate-resistant mutants has primarily focused on those which are nitrate reductase-deficient. Chlorate-resistant mutants which possess nitrate reductase activity have been identified, and a number of alternative mechanisms of resistance have been discussed (Oostindier-Braaksma and Feenstra 1973, Cove 1979, Murphy et al 1985), There appears to be, however, only two published reports characterizing chlorate uptake mutants. Doddema and Telkamp (1979) reported that a chlorate-resistant, CIO; uptake mutant of Arabidopsis thaliana was impaired in NO; uptake relative to the wild type at higher nitrate concentration ranges.…”
Section: Resultsmentioning
confidence: 99%